Developing a Burn-Specific Family-Centered Care (BS-FCC) Framework: A Multi-Method Study - Jonathan Bayuo; Anita Eseenam Agbeko (European Burn Journal, 2023)
A burn has been described as a family injury warranting the delivery of family-centered care (FCC) across the continuum of burns management. This assertion notwithstanding, only limited progress has been made to develop and implement FCC interventions in the burn unit. As a starting point, this study sought to formulate a tentative framework to underpin FCC in burn care. A multi-method design comprising an umbrella review and the secondary data analysis of qualitative datasets was employed. Following these, the findings were merged and aligned to the Universal Model of FCC to formulate the burn-specific FCC framework. For the umbrella review, four review articles met the criteria for inclusion. Following a data synthesis of the review findings and their integration with the qualitative dataset, four meta-themes that encapsulate the shared needs/concerns of family members of both pediatric and adult burn survivors emerged: (1) psychosocial concerns, (2) issues relating to role changes, (3) logistical concerns, and (4) requiring information. These issues were mapped to the following components of the Universal Model of FCC: family support, education, collaboration, and communication. All these are underpinned by dedicated policies, procedures, and consideration of the family context. Testing and further empirical work are needed to refine and implement the framework across the continuum of burn management.